1985
DOI: 10.1002/for.3980040208
|View full text |Cite
|
Sign up to set email alerts
|

An experiment to evaluate methods for estimating fossil fuel resources

Abstract: Estimates of petroleum and natural gas resources vary substantially, both over time and across estimation methods. This paper develops a simulation model of global oil resources to evaluate different resource estimation techniques. Protocols for the Hubbert life cycle and USGS geological analogy methods are developed and applied to synthetic data generated by the model. It is shown that the Hubbert method can generate an accurate estimate as early as twenty years before the peak of global production, but the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…In reality, the upstream activities are conducted by nationally owned companies. This assumption is similar to the work by Naill [12] and Sterman et al [17]. The upstreaming activities are modeled based on the total life-cycle which is comprised of exploration, development and production phases.…”
Section: Sd Model Of Upstream Natural Gas Investmentmentioning
confidence: 98%
See 1 more Smart Citation
“…In reality, the upstream activities are conducted by nationally owned companies. This assumption is similar to the work by Naill [12] and Sterman et al [17]. The upstreaming activities are modeled based on the total life-cycle which is comprised of exploration, development and production phases.…”
Section: Sd Model Of Upstream Natural Gas Investmentmentioning
confidence: 98%
“…Following the same path, the use of SD methodology for the understanding of complex energy systems has increased significantly. Sterman was involved in the conversion of FOSSIL1 to FOSSIL2, a model that includes feedback from within the economy and energy system [16,17]. The SD modelling approach is very popular in literature on the energy sector and it has also been applied to many countries, such as the United States, UK, Argentine and so on [18][19][20][21].…”
Section: State Of Literaturementioning
confidence: 99%
“…To find the accurate forecasting method, they created a system dynamics model and compared Hubbert life cycle and USGS geologic analogy method in simulation results. To do so, they used a synthetic data experiment and found that Hubbert's method was clearly the most accurate (Sterman and Richardson, 1985). Afterward, the model was used to evaluate the amount of ultimately recoverable oil in US (Sterman, Richardson and Davidsen, 1988).…”
Section: The Review Of Main System Dynamics Models Of Fossil Fuel Resmentioning
confidence: 99%
“…Chi, Nuttall, and Reiner (2009), based on Naill (1973;1977) and Sterman and Richardson (1985), developed a system dynamics model of Natural gas system in UK to investigate the main effective factors on the long-term supply and demand and study the nature of the system's behavior; furthermore, the effect of different policies about the growing of import-dependence on unstable exports in the next decades were studied. Finally, they found that supply-side policies alone cannot effectively postpone the peaks in discovery, production, and consumption; Also, the reduction of UK's dependence on gas imports, a combination of domestic and international policies (about exporters), could be useful.…”
Section: The Review Of Main System Dynamics Models Of Fossil Fuel Resmentioning
confidence: 99%
“…The approach is based on the use of synthetic data generated by a model of the processes being forecasted (Richardson 1982, Sterman andRichardson 1985).…”
Section: D-3887mentioning
confidence: 99%